Brand identification and sense of security: the polarity of customer loyalty in Ukraine’s banking sector - KIIKO, Yurii (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2025)
Background. In the realm of digital transformation and escalating consumer expectations within Ukraine’s banking sector, comprehending the psychological factors influencing loyalty has gained paramount significance. Conventional elements such as service ease and cost are inadequate to secure enduring consumer loyalty. Contemporary consumers prioritize emotional engagement, perceived security, and psychological reassurance in their financial dealings. This study examines the influence of five fundamental factors–brand identity, sense of security, trust, emotional attachment, and pride – on customer loyalty, particularly regarding their propensity to suggest their bank to others. Methods. A quantitative analysis was performed via an online CAWI survey with 251 active banking clients in Ukraine. The instrument comprised original multi-item scales with high internal consistency (Cronbach’s alpha > .78). The data were examined utilizing descriptive statistics, Spearman’s correlation, one-way ANOVA, and binary logistic regression. Loyalty predictors were evaluated across different banking institutions, including PrivatBank and Monobank. Results. The sense of security (Exp(B) = 2.256) and emotional attachment (Exp(B) = 1.676) emerged as the most important predictors of loyalty. Brand identification was significant solely for Monobank (Exp(B) = 7.069), but for PrivatBank, security prevailed. The quantity of client touchpoints exerted a consistently detrimental impact on loyalty. Loyalty levels fluctuated according to age, income, and the customer’s principal banking institution. Conclusions. Customer loyalty in Ukraine’s banking sector is established through a blend of rational variables (e.g., security and contentment) and emotional aspects (e.g., identification and connection). Conventional banks often depend on a rational loyalty framework, but neobanks such as Monobank thrive on a more emotionally motivated paradigm. These findings offer insights for formulating client-centered tactics that integrate psychological comfort and emotional branding to enhance loyalty.